Myosin IIB assembly state determines its mechanosensitive dynamics - Schiffhauer, Eric S. (J Cell Biol, 2019)
Dynamical cell shape changes require a highly sensitive cellular system that can respond to chemical and mechanical inputs. Myosin IIs are key players in the cell’s ability to react to mechanical inputs, demonstrating an ability to accumulate in response to applied stress. Here, we show that inputs that influence the ability of myosin II to assemble into filaments impact the ability of myosin to respond to stress in a predictable manner. Using mathematical modeling for Dictyostelium myosin II, we predict that myosin II mechanoresponsiveness will be biphasic with an optimum established by the percentage of myosin II assembled into bipolar filaments. In HeLa and NIH 3T3 cells, heavy chain phosphorylation of NMIIB by PKCζ, as well as expression of NMIIA, can control the ability of NMIIB to mechanorespond by influencing its assembly state. These data demonstrate that multiple inputs to the myosin II assembly state integrate at the level of myosin II to govern the cellular response to mechanical inputs.